Association between white blood cell count and adverse pregnancy outcomes: a retrospective cohort study from a tertiary hospital in China - Yu Zhang; Xuesong Li; Zheng Hu; Yuping Song; Yiling Qian; Chuanwei Liu; Xiaofang Fan; Yujuan Fan; Jialin Yang (BMJ Open)
Objectives This study aimed to clarify the relationship between white blood cell (WBC) and adverse pregnancy outcomes.Design A total of 25 270 pregnant women underwent peripheral blood white blood cell count tests in the first, second and third trimesters. Adverse pregnancy outcomes were gestational hypertension, pre-eclampsia, gestational diabetes mellitus, preterm birth, low birth weight, caesarean delivery, macrosomia and fetal distress. Due to acute infectious disease or other diseases, 1127 were excluded.Setting Minhang Hospital, China.Participants A total of 24 143 pregnant women were included in this study.Primary and secondary outcome measures The primary outcome was the adverse pregnancy outcomes.Results For the 24 143 participants, we calculated adjusted ORs for adverse pregnancy outcomes associated with an increased WBC count. For gestational hypertension, the ORs were 1.18 (95% CI, 1.05 to 1.24) in the first trimester and 1.10 (1.06 to 1.13) in the second trimester; for pre-eclampsia, ORs were 1.14 (95% CI, 1.47 to 1.64) in the first trimester and 1.10 (1.05 to 1.16) in the second trimester; for gestational diabetes mellitus, ORs were 1.06 (95% CI, 1.00 to 1.13) in the first trimester and 1.10 (1.04 to 1.16) in the second trimester; for preterm birth, ORs were 1.12 (95% CI, 1.06 to 1.18) in the first trimester, 1.10 (1.06 to 1.13) in the second trimester and 1.12 (1.09 to 1.15) in the third trimester; for low birth weight, ORs were 1.09 (95% CI, 1.02 to 1.17) in the first trimester, 1.03 (0.99 to 1.08) in the second trimester and 1.12 (1.08 to 1.16) in the third trimester. Significant associations were not observed obviously for caesarean delivery, macrosomia and fetal distress.Conclusions Our results indicate strong, continuous associations of maternal WBC count with increased risks of adverse pregnancy outcomes.